(untitled) (Journal of Medical & Health Sciences Review, 2025)
Silybum marianum (milk thistle) seeds contain a flavonoid-rich extract that has been used for liver disorders. However, it has not been extensively studied for its analgesic, anti-inflammatory, diuretic, and antidiarrheal properties. We tested an ethanolic seed extract (SME) in standard rodent models. Swiss albino mice and Wistar rats (n=8) were divided into three groups: control, standard drug, and SME-treated (100, 200, 400 mg/kg p.o.). Sample sizes were determined using power analysis (α=0.05, β=0.2) based on preliminary variability. The study evaluated analgesic activity through acetic acid writhing (visceral pain) and tail-flick (thermal nociception), as well as anti-inflammatory activity through carrageenan-induced paw edema, diuretic activity through 24-hour urine output and electrolyte excretion (versus furosemide), and antidiarrheal activity through castor oil-induced diarrhea (versus loperamide). The extract significantly reduced writhing counts (73% inhibition at 400 mg/kg, p<0.01) and prolonged tail-flick latency, comparable to aspirin. Carrageenan-induced paw edema was dose-dependently suppressed, with 46% inhibition at 400 mg/kg (vs. 48% by aspirin) at 4 hours (p<0.01). SME showed moderate increases in urine volume (96% at 400 mg/kg, p<0.05) and natriuresis, but not as much as furosemide (156% increase, p<0.001). In the antidiarrheal test, the extract delayed diarrhea onset and decreased fecal output (70% reduction at 400 mg/kg, p<0.01). There was no overt toxicity observed. Phytochemical profiling (HPLC) revealed that SME contains silibinin ( 60%), silychristin ( 10%), silydianin ( 10%), isosilybins ( 5%), and taxifolin ( 5%) [6,17]. S. marianum seed extract has analgesic, anti- inflammatory, mild diuretic, and antidiarrheal properties. The flavonoid composition correlates with the multi-modal bioactivity. This preclinical profile suggests that S. marianum seeds could be used as a phytomedicine to treat pain, inflammation, and gastrointestinal disturbances, necessitating further mechanistic and clinical research.